Investigative private policing beyond the police: an exploratory study - Button, Mark (Policing and society, 2023)
This paper is based on a survey of 331 private investigators predominantly based or working in the UK. It offers findings on the background, roles undertaken, tools used and outcomes of their work. It divides the investigators into four main groups: private investigators (or detectives), investigators working for forensic accountants, in-house private investigators and in-house public investigators (non-police). Given the lack of research on this segment of private policing, important exploratory findings are presented which can be used as the foundations of further research in this rarely investigated sector. The paper illustrates the dominance of older men in second careers among private investigators, the dominance of fraud investigation as the most common work undertaken and limited involvement in surveillance. The paper also presents significant findings on the number of persons who face some form of justice as a result of their investigations.